A Critical Evaluation of Vitamin D (IntechOpen, 2023)
Vitamin D, a fat-soluble vitamin, also called as "sunshine vitamin" is derived mostly from sun exposure and food, and for normal activation, it has to undergo two hydroxylation reactions. Vitamin D affects more than 2000 genes in the body. Serum level of 25(OH) D is an ideal indicator of vitamin D status in our body. Vitamin D deficiency leads to various diseases. On a therapeutic point of view, vitamin D helps to treat many diseases. The book "A Critical Evaluation of Vitamin D - Clinical Overview" targets the principles, mechanisms, and clinical significance of vitamin D. This book covers four sections: "Vitamin D in Cardiovascular and Renal Diseases", "Vitamin D in Age and Neurological Diseases", "Vitamin D and Cancer" and "Therapeutic Measurements of Vitamin D". Each of these sections is interwoven with the theoretical aspects and experimental techniques of basic and clinical sciences. This book will be a significant source to students, scientists, physicians, healthcare professionals and also other members of this society who are interested in exploring the role of vitamin D in human life. [Vitamin D can be considered as vitamin of "defense" since it cures several diseases. - Sivakumar Gowder]